PERSONAL CHARACTERISTICS AND ANXIETY OF STUDENTS AGAINST THE BACKGROUND OF THE COVID-19 PANDEMIC IN UKRAINE - Korovina, L.D.; Zaporozhets, T.M.; Silkova, O.V. (World of Medicine and Biology, 2022)
The purpose of the study was to investigate the level, state and signs of student anxiety in the COVID-19 pandemic, to identify the most significant factors associated with potential problems in these conditions, to investigate the relationship between anxiety, and individual psychological characteristics of students and autonomic nervous system disorders. systems. In December 2020 – to January 2021, an online survey was conducted to study the personal and situational anxiety, neuroticism and individual psychological orientation of H. Eysenck, the presence of autonomic nervous system dysfunction according to A.M. Wein and determine the level of specific anxieties caused by the pandemic. Until the end of the first year of the COVID-19 pandemic, we observed increased levels of situational and personal anxiety in medical students. In turn, the level of neuroticism was typical of this social group. Extraversion has decreased compared to the pre-pandemic period. The level of neuroticism correlated with anxiety about the risk of infection of family members of COVID-19, and the level of personal anxiety correlated with anxiety about their own risk of infection with COVID-19. The state of autonomic regulation remained at the level of the pandemic period.
Keywords: students; pandemic COVID-19; anxiety; neuroticism; autonomic nervous system